(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This article presents the idea of an m-polar fuzzy KU-ideal and investigates its characteristics. The relationship between an m-polar fuzzy KU-subalgebra and an m-polar fuzzy KU-ideal is presented in the discussion